12x-11x+5=-(x+3)+5

Simple and best practice solution for 12x-11x+5=-(x+3)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-11x+5=-(x+3)+5 equation:


Simplifying
12x + -11x + 5 = -1(x + 3) + 5

Reorder the terms:
5 + 12x + -11x = -1(x + 3) + 5

Combine like terms: 12x + -11x = 1x
5 + 1x = -1(x + 3) + 5

Reorder the terms:
5 + 1x = -1(3 + x) + 5
5 + 1x = (3 * -1 + x * -1) + 5
5 + 1x = (-3 + -1x) + 5

Reorder the terms:
5 + 1x = -3 + 5 + -1x

Combine like terms: -3 + 5 = 2
5 + 1x = 2 + -1x

Solving
5 + 1x = 2 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
5 + 1x + x = 2 + -1x + x

Combine like terms: 1x + x = 2x
5 + 2x = 2 + -1x + x

Combine like terms: -1x + x = 0
5 + 2x = 2 + 0
5 + 2x = 2

Add '-5' to each side of the equation.
5 + -5 + 2x = 2 + -5

Combine like terms: 5 + -5 = 0
0 + 2x = 2 + -5
2x = 2 + -5

Combine like terms: 2 + -5 = -3
2x = -3

Divide each side by '2'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 189-y=272 | | (3x+7)=(2x+3) | | (x*5)-x=600 | | 216=-u+129 | | 2(3)+3y=5 | | .0001/125 | | 2845=48x-563 | | 4x-2=2x+36 | | 4(2a+5)+4=3(5a-6) | | 22x+81=147 | | 0=12-5lnx | | 66x+339=2715 | | 24+32p=x | | 2x+5x-3=9 | | 66x+339=2719 | | 5x-73=117 | | 36+5x=91 | | 16r^2-r=0 | | 5a-10-3a=4a-a+16-3a | | 2x^3-4x^2+3x+9=0 | | (2-6)(3-6)=70 | | (x+1)(x-5)+5=0 | | 12u-6u=36 | | a=-2b+-3c | | 4x+125=180 | | 18-(2m+8)=5+2m-15 | | 2x^2-33x+126=0 | | 6=z/7.8 | | 13.96+0.11(x+3)=14.71-0.07x | | -4y=0+8x+12 | | 7.6x=-1.824 | | 0.6A+15=7.2 |

Equations solver categories